Neuropilin-1 Binding Peptide as Fusion to Diphtheria Toxin Induces Apoptosis in Non-small Cell Lung Cancer Cell Line - Eghtedari, Sara; Behdani, Mahdi; Kazemi-Lomedasht, Fatemeh (Current pharmaceutical design, 2024)
Targeted cancer therapy can be considered as a new strategy to overcome the side effects of current cancer treatments. Neuropilin-1 (NRP-1) is a transmembrane glycoprotein that is expressed in endothelial cells and tumor vessels to stimulate angiogenesis progression. Targeted diphtheria toxin (DT)- based therapeutics are promising tools for cancer treatment. This study aimed to construct a novel NRP-1 binding peptide (as three repeats) (CRGDK) as a fusion to truncated DT (DTA) (DTA-triCRGDK) for targeted delivery of DT into NRP-1 expressing cells. The concept of DTA-triCRGDK was designed, synthesized and cloned into the bacterial host. Expression of DTA-triCRGDK was induced by Isopropyl ß-D-1-thiogalactopyranoside (IPTG) and purification was performed using Ni-NTA chromatography. Biological activity of DTA-triCRGDK was evaluated using MTT, apoptosis, and wound healing assays. In addition, expression levels of apoptotic Bax, Bcl2, and Casp3 genes were determined by Real-time PCR. Cytotoxicity analysis showed the IC values of DTA-triCRGDK for A549 and MRC5 were 0.43 nM and 4.12 nM after 24 h, respectively. Bcl2 expression levels decreased 0.4 and 0.72 fold in A549 and MRC5, respectively. However, Bax and Casp3 expression level increased by 6.75 and 8.19 in A549 and 2.51 and 3.6 in MRC5 cells. Taken together, DTA-triCRGDK is a promising tool for targeted therapy of NRP-1 overexpressing cancer cells.